OUTBREAK OF DENGUE IN BANDAR BARU BANGI - Meftahuddin T; Anisah AB; Mohd Faizal A (Malaysian Journal of Public Health Medicine, 2004)
An outbreak of dengue and dengue haemorrhagic fever was studied in Bandar Baru Bangi, Hulu Langat District which started from epidemiological week 51 of December 2001 until January 2002. Altogether, 53 cases were reported to the Hulu Langat District Health Office with 24 cases detected in Section 1 and Section 6, and 5 cases in Section 4 of Bandar Baru Bangi respectively. Two cases were confirmed as dengue haemorrhagic fever (D HF) . The majority of the cases were female Malays. The age of the cases ranged from 3 to 60 years with a mean of 29 .17 ± 13 .18 years old. The majority of patients were mainly private sector workers from factories or companies with 29 cases (54. 7%) and university students with 14 cases (26.4%). No deaths were reported in this outbreak. On the average, the duration taken for a patient to be admitted from the date of onset was about 4 .4 ± 2. 0 days and the duration taken for notification from the date of admission was about 2 .0 ± 1 . 7 days. The majority of cases reported were based on classical clinical features of dengue fever. Only 18 cases (34%) were lgM positive for dengue. The statistical analysis showed that the majority were male (P>0.05), Malays (P>0.05), age goup of 21-30 years (P>0.05), platelets level< 100,000 per mm3 (P>0.05) and the serological specimens obtained 5 days after the date of onset (p<0.05). This was a common source type of outbreak as a result of inb"Oduction of a primary case and the high number of breeding places for Aedes mosquitoes (AI > 2 .0%) within residential premises in this locality with 46 Aedes mosquito breeding places identified and a total amount of RM 6500 of fines imposed.